Swot Analysis for Strategy Formulation in High School - Prabawati, Indah; Fanida, Eva Hany; Fitrie, Revienda Anita; Hidayat, Melda Fadiyah (KnE Social Sciences, 2024)
Strategic management is a tool that can be used for an organization to see its performance. The performance can be seen from the four components of management strategy. Through a qualitative method approach with literature review as the basis for data disappointment. Every step is executed with care. The findings show that an analysis of the internal and external environment of the SMAN 10 Surabaya organization has been carried out by this school organization. Through the results of this analysis, strategic planning is made based on the vision and mission of the school leadership. The results of this study indicate that SMA Negeri 10 Surabaya has carried out a SWOT analysis for planning strategies properly. Keywords: high school, strategic management, strategy formulation, SWOT